Toward Black Girl Futures: Rememorying in Black Girlhood Studies. Issue 3 (1st December 2022) - Smith-Purviance, Ashley L.; Jackson, Sara; Harper, Brianna; Merandisse, Jennifer; Smith, Brittney; Hussey, Kim; Lopez, Eliana
Abstract: Black Girlhood Studies provide an authentic vantage point for the narratives and experiences of young Black girls today. Black women working alongside Black girls play a central role in the development of the field, yet their narratives and experiences as former Black girls remain decentered. Using autoethnography, we describe the experiences of seven community-engaged Black women scholars, including one professor who teaches Black Girlhood Studies courses and is the co-creator of a virtual space for middle school Black girls called Black Girl Magic (BGM), and six undergraduate students who are enrolled in the course and/or serve as BGM co-facilitators. We discuss how teaching, learning, and practicing Black Girlhood Studies shapes a collective rememorying process for Black women seeking to make their girlhood experiences legible.